Physical and Chemical Properties of Chicken Sausage with The Addition of Dayak Onion (Eleutherine palmifolia (L) Merr) from Central Kalimantan - Monasdir; Nugroho, Antonius Adhityawan; Riskayanti; Husein, Firdaus; Nisfimawardah, Lailatun; Astuti, Erlina; Setyowati, Eka Agustin Hayu; Nio, Maria Magdalena (Faculty of Animal Science Universitas Brawijaya, 2024)
This study aims to analyze the physical and chemical properties of chicken sausages with the addition of dayak onions (Eleutherine palmifolia (L) Merr) from Central Kalimantan. The experimental design used in this study was a completely Randomized Design consisting of 2 treatments and 3 replications with differences in the concentration of adding fresh dayak onions it consists of T0 (chicken sausage without the addition of dayak onions), T1 (chicken sausage + 2% dayak onion) and T2 (chicken sausage + 4% dayak onion). Variables observed contain physical properties of chicken sausages (pH and aw value). Chemical and antioxidant properties of dayak onion sausage (moisture content, protein content and antioxidants) as well as sausage texture profile (hardness, compactness, gumminess, elasticity and chewiness). Data on physical, chemical, antioxidant characteristics and texture profiles of chicken sausages with the addition of dayak onions were analyzed using ANOVA and further tested using the Tukey Test. The results showed that chicken sausage with the addition of dayak onions at different levels had an effect on the value of pH, aw, water content, protein content, antioxidants and texture profile. The addition of dayak onions increases the antioxidant levels of chicken sausages and makes the color bright red compared to without the addition of dayak onions.